Reformator i statysta albo hulaka na metafizyczną skalę. O dwóch portretach cara Iwana Groźnego w kinie rosyjskim - Andrzej Szpulak (Images)
Reformer and Outstanding Politician or Rake on a Metaphysical Scale. Two Portraits of Tsar Ivan the Terrible in Russian Cinema